A Conversation with ... Kangni Alem (A Conversation with ..., 2026)
The interview “A Conversation with … Kangni Alem” features a discussion between Thierry Boudjekeu and Laude Ngadi with the Togolese writerKangni Alem, who visited the University of Bayreuth in May 2025 for the workshop “From Oblivion to Memory: Transatlantic Memorial Echoes.” During the conversation, Kangni Alem reflects on the role of literature in preserving memory and confronting historical silences. He discusses how transatlantic histories—especially those connected to colonialism, migration, and cultural exchanges between Africa and the diaspora—shape contemporary identities and narratives. Alem emphasizes the importance of storytelling as a tool to recover forgotten voices and to bridge past and present. — L’entretien « A Conversation with … Kangni Alem » présente un échange entre Thierry Boudjekeu et Laude Ngadi avec l’écrivain togolais Kangni Alem invité à l’Université de Bayreuth en mai 2025 pour participer à l’atelier « From Oblivion to Memory: Transatlantic Memorial Echoes ». Au cours de la discussion, Kangni Alem réfléchit au rôle de la littérature dans la préservation de la mémoire et dans la mise en lumière d’histoires souvent réduites au silence. Il aborde la manière dont les histoires transatlantiques—liées notamment au colonialisme, aux migrations et aux échanges culturels entre l’Afrique et sa diaspora—façonnent les identités et les récits contemporains. — Find out more about the project "Black Atlantic Revisted" at the Africa Multiple Cluster of Excellence hier: https://www.africamultiple.uni-bayreuth.de/en/1_2-Research/Research-Projects/Arts-and-Aesthetics/Black-Atlantic-revisited/May-Exhibition/index.html